Research on Key Issues of Consistency Analysis of Vehicle Steering Characteristics - Yanhua Liu; Xin Guan; Pingping Lu; Rui Guo (Chinese Journal of Mechanical Engineering, 2021)
Abstract Given the global lack of effective analysis methods for the impact of design parameter tolerance on performance deviation in the vehicle proof-of-concept stage, it is difficult to decompose performance tolerance to design parameter tolerance. This study proposes a set of consistency analysis methods for vehicle steering performance. The process of consistency analysis and control of automotive performance in the conceptual design phase is proposed for the first time. A vehicle dynamics model is constructed, and the multi-objective optimization software Isight is used to optimize the steering performance of the car. Sensitivity analysis is used to optimize the design performance value. The tolerance interval of the performance is obtained by comparing the original car performance value with the optimized value. With the help of layer-by-layer decomposition theory and interval mathematics, automotive performance tolerance has been decomposed into design parameter tolerance. Through simulation and real vehicle experiments, the validity of the consistency analysis and control method presented in this paper are verified. The decomposition from parameter tolerance to performance tolerance can be achieved at the conceptual design stage.